Heart rate response to "off-road" running events in female athletes. Issue 1 (March 1998) - Creagh, U; Reilly, T; Nevill, A M
Abstract : INTRODUCTION: Despite the growing popularity of off-road running events, little information is available about the physiological stress of such activities. The demands of such events are unique in terms of the rough surface of the terrain encountered as well as the underfoot vegetation and the gradient. OBJECTIVES: The aim of this study was to investigate the physiological response of female athletes, as measured by heart rate, to three common off-road running events: cross country running (n = 15), fell running (n = 20), and orienteering (n = 25). METHODS: Heart rate responses were recorded during cross country and fell races, and orienteering by means of short range radiotelemetry. Road running (n = 21) was also studied as a reference. RESULTS: The mean heart rates for each event varied with the differing demands of the terrain. The highest (182 (10) beats/minute; mean (SD)) was for road running and the lowest (172 (10) beats/minute) for orienteering. Orienteering evoked a significantly more variable response than all other events (F4, 100 = 112.4; p<0.01), with a range of 44 beats/minute (142-186 beats/minute) in the heart rate. This may be due to both the variability of the terrain and the additional technical aspect of this sport. There was a positive trend in the slope of the regression lines of heart rate against time for both road and cross country running, which was not evident in the fell runners or the orienteers. The latter events demonstrated no consistent pattern. CONCLUSIONS: It is concluded that running off-road elicits a heart rate response that varies with the altering demands of surface, vegetation, and gradient.